Optimizing lavage during knee arthroscopy: A three‐dimensional MRI study. Issue 1 (31st August 2012) - Nord, Russell M.; Badowski, Natalie; Elkins, Christopher; Alley, Marcus; Harris, Alex H.S; Dragoo, Jason L.
Abstract Purpose: To determine the best positioning and the resulting fluid flow patterns inside the knee during arthroscopy, reducing the surgical morbidity associated with the arthroscopic irrigation and debridement of a septic knee joint. Materials and Methods: Three‐dimensional MRI, using an MRI‐compatible human cadaveric knee arthroscopic model, generated fluid flow diagrams and velocity vector data. This was analyzed for six different arthroscopic configurations and at six different locations within the knee joint. Results: At any one static arthroscopic position, fluid flow velocity differed at the various locations in the knee, often with statistically significantly greater flow at one location over another. In general, flow was greatest at the location at which the inflow cannula terminated and preferentially flowed directly to the outflow cannula location, neglecting spaces in the knee that were not on this direct path. Three‐portal arthroscopy provided no benefit over two‐portal arthroscopy. Conclusion: To maximize arthroscopic lavage throughout all compartments in the knee, the arthroscopist must individually enter each space in the knee. Static arthroscopy in the setting of knee sepsis may lead to inadequate flow in certain areas of the knee and may lead to treatment failure. Three‐portal arthroscopy does not improve lavage efficiency. J. Magn. Reson. Imaging 2013;37:201–207. © 2012 Wiley Periodicals, Inc.